Natural Law in Editions of the 18th Century from the Library of the Irkutsk Theological Seminary as a Historical Source - O. A. Ovchinnikova; O. V. Moreva (Библиосфера)
The article gives a historical and book review of Western European publications of the XVIII century on natural law, preserved in the Scientific Library of the Ural State Law University (previously in the collection of the library of the Irkutsk Theological Seminary). Books are considered as a complex historical source with an inexhaustible source-study potential for studying the history of book culture. The facts of the history of the formation of the Irkutsk Theological Seminary library fund at the end of the XVIII – early XIX century and the geography of the spread of the ideas of lawyers of Western Europe, obtained by studying readers’ records, library labels and book signs, are presented. The article not only presents bibliographic descriptions of book rarities of the Enlightenment era (five books in 13 volumes), but also describes in detail all traces of their existence. As a result of the study, the picture of the development of book distribution, librarianship and reading in Siberia in the XVIII–XIX centuries is supplemented.